Effect of Intellectual Intelligence, Emotional Intelligence, And Work Discipline on Employee Performance (A Study on Employee PT. AmanahAnugerah Adi Mulia Banjarmasin) - Ray Melvin Resubun; Ahmad Alim Bahri; Dahniar (JWM (JURNAL WAWASAN MANAJEMEN), 2020)
This research aims to analyze the effect of intellectual intelligence (X1), emotional intelligence (X2), and work discipline (X3) as independent variables on employee performance (Y) as the dependent variable on employees of PT. AmanahMuliaAnugerah Adi Banjarmasin. This research method uses a questionnaire with a population of 35 employees of PT. Banjarmasin Adi MuliaAnugerah mandate which was taken as a research sample. Variable measurement technique using Likert scale with weighting scale from 1 to 5. The analysis technique used in testing the hypothesis in this study using multiple regression analysis. The result of research concludes that there was no significant influence on the variables of intellectual intelligence and emotional intelligence on employee performance, there was a significant influence between the variables of work discipline on employee performance.